Time Performance Analysisi of Hotel Building Construction Project Using Performance Intensity Method - Wina Destryan; Siti Nurasiyah; Naufal Ariq Pratama (Portal: Jurnal Teknik Sipil, 2025)
In project implementation, both owners and contractors place great emphasis on timely completion. However, project delays often occur, necessitating an effective time performance analysis method to minimize the risk of delays. Therefore, a project time performance analysis was conducted by comparing actual field data with the initial plan. This study used a quantitative descriptive approach by analyzing variables from field observation data. The project was scheduled for completion on December 30, 2025, with a duration of 514 calendar days. The analysis was conducted in the 35th and 48th weeks of project implementation. The results in the 35th week showed a slower project completion prediction, namely around February 22, 2026. However, in the 48th week, the project was estimated to be completed earlier, namely on December 27, 2025, where the contractor could save 0.37% of the overall progress of the plan that had been implemented.Â